2020
DOI: 10.1021/acs.accounts.0c00244
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Ylides/Carbenes and Related Intermediates from Phosphonium/Sulfonium Salts

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Owing to the special effects of the fluorine element, including high electronegativity and small atomic radius, the incorporation of a fluorinated group into organic molecules may modify their physical, chemical, and biological properties.Fluorine-containing compounds have found widespread application in a variety of areas, and thus, the development of efficient reagents and methods for the incorporation of fluorinated groups has become a subject of significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…Fluorinated ylides are common in organofluorine chemistry as reagents or reactive intermediates [16] . During the last few years, difluomethylene phosphonium ylides have found wide applications as nucleophilic fluoroalkylation reagents in the transformation of many electrophiles including carbonyl compounds [9g, 16b, 17] . In this context, we speculated that the nucleophilic aminodifluoromethylation of carbonyl compounds with difluorocarbene could be tamed by the addition reaction of difluomethylene ammonium ylides [18] in‐situ generated from tertiary amines and difluorocarbene followed by the selective removal of one alkyl substitute from the quaternary ammonium salt intermediates (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorinated ylides are common in organofluorine chemistry as reagents or reactive intermediates [16] . During the last few years, difluomethylene phosphonium ylides have found wide applications as nucleophilic fluoroalkylation reagents in the transformation of many electrophiles including carbonyl compounds [9g, 16b, 17] . In this context, we speculated that the nucleophilic aminodifluoromethylation of carbonyl compounds with difluorocarbene could be tamed by the addition reaction of difluomethylene ammonium ylides [18] in‐situ generated from tertiary amines and difluorocarbene followed by the selective removal of one alkyl substitute from the quaternary ammonium salt intermediates (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the explosive nature of CF 3 CHN 2 , it is desirable to develop a safe and convenient trifluoromethylcarbene reagent. We have been interested in the development of fluorinated phosphonium/sulfonium salts as fluorinated carbene reagents [41] . Based on our previous observation that phosphonium ylide Ph 3 P + −CF 2 − could directly undergo a P−C bond cleavage to release difluorocarbene, [42] we originally thought that sulfonium ylide Ph 2 S + −CH − CF 3 may also be able to generate trifluoromethylcarbene via a S−C bond cleavage.…”
Section: Cf3‐cyclopropanesmentioning
confidence: 99%
“…We have been interested in the development of fluorinated phosphonium/sulfonium salts as fluorinated carbene reagents. [41] Based on our previous observation that phosphonium ylide Ph 3 P + À CF 2 À could directly undergo a PÀ C bond cleavage to release difluorocarbene, [42] we originally thought that sulfonium ylide Ph 2 S + À CH À CF 3 may also be able to generate trifluoromethylcarbene via a SÀ C bond cleavage. However, deep investigations revealed that the bond cleavage cannot directly occur.…”
Section: [Ph 2 S + Ch 2 Cf 3 ] Tfo à As a Trifluoromethylcarbene Sourcementioning
confidence: 99%
“…We previously used Selectfluor, one of the most commonly used “F + ” reagents, to achieve dehydroxylative fluorination of tertiary alcohols, allowing for the formation of tertiary C−F bonds [10] . In continuation of our research interest in fluorine incorporation, [11] we have now investigated the anti ‐Markovnikov iodofluorination of alkenes with Selectfluor. Compared with the above anti ‐Markovnikov methods, our protocol features convenient operations, simple reaction conditions, a wide substrate scope, and the installation of an iodine atom which provides possibilities for further transformations (Scheme 1, eq 3).…”
Section: Introductionmentioning
confidence: 99%